2017
DOI: 10.1016/j.jpainsymman.2016.12.351
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Yoga for Children Hospitalized With Sickle Cell Vaso-Occlusive Crisis

Abstract: This study provides evidence that yoga is an acceptable, feasible, and helpful intervention for hospitalized children with VOC. Future research should further examine yoga for children with SCD pain in the inpatient and outpatient settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
81
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(81 citation statements)
references
References 45 publications
0
81
0
Order By: Relevance
“…Eleven AEs could not be rated for severity due to insufficient information ( Table 2 ) [ 30 , 32 , 34 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven AEs could not be rated for severity due to insufficient information ( Table 2 ) [ 30 , 32 , 34 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…While there are systematic reviews that have extracted AE information on individual MB therapies [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ], few of these have addressed AE as a primary objective [ 52 , 53 , 54 , 55 ]. Within the reviews with AE as a primary outcome, only three adverse events related to MB therapies were captured [ 34 ], in comparison to our review which was able to identify 37 adverse events. This synthesis helps to fill the existing gap in pediatric MB therapy research.…”
Section: Discussionmentioning
confidence: 99%
“…Selected articles were published between 2006 and 2018. Twenty-one of the 27 studies were conducted in the United States (36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55), two were conducted in India (56, 57), and one each in Germany (58), Canada (59), Iran (60), and Colombia (61). See Tables 1-3 for details regarding studies assessing both symptoms of anxiety and depression (Table 1), symptoms of anxiety (Table 2), and symptoms of depression (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies were RCT (37,39,42,43,50,52,56,59,61,62), 15 were cohort studies (36, 40, 44-49, 51, 52, 54, 55, 57, 58, 60), and two were cohort analytic (38,41). Control and comparison group activities varied significantly across studies.…”
Section: Types and Quality Of Studiesmentioning
confidence: 99%
“…There was also a significant decrease in joint pain pre/post sessions. Moody et al (2017) recently reported the use of yoga as a nonpharmacological intervention to reduce pain in children hospitalized with vaso-occlusive crisis. In their study, patients were offered daily yoga sessions, which included mindfulness, poses, breathing instructions, and guided relaxation, compared with a similar control group, which was offered relaxation music.…”
mentioning
confidence: 99%